2013
DOI: 10.1371/journal.pone.0061393
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vascular Smooth Muscle Cell Proliferation by Gentiana lutea Root Extracts

Abstract: Gentiana lutea belonging to the Gentianaceae family of flowering plants are routinely used in traditional Serbian medicine for their beneficial gastro-intestinal and anti-inflammatory properties. The aim of the study was to determine whether aqueous root extracts of Gentiana lutea consisting of gentiopicroside, gentisin, bellidifolin-8-O-glucoside, demethylbellidifolin-8-O-glucoside, isovitexin, swertiamarin and amarogentin prevents proliferation of aortic smooth muscle cells in response to PDGF-BB. Cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Additionally it has been shown that both catechins and EGCG suppress PDGF-BB induced activation of PDGF-receptor mediated signal transduction pathways in VSMC by blocking tyrosine phosphorylation and their downstream molecular targets [ 99 ]. These findings are consistent with our recent study on antiproliferative effect of Gentiana lutea and its main constituent isovitexin where Kesavan et al have reported aqueous root extract of G. lutea and isovitexin significantly inhibit PDGF-BB induced proliferation of SMC by downregulation of ERK1/2 and iNOS expression [ 100 ]. Similarly in another study we have shown significant antiproliferative effect of ellagic acid (EA), phenolic compound present mainly in barriers, which might be due to prevention of PDGF-BB receptor tyrosine phosphorylation/activation, reduced ROS generation, and downstream stimulation of ERK1/2 [ 101 ].…”
Section: Role Of Phytochemicals In Cell Migration and Proliferatiosupporting
confidence: 93%
“…Additionally it has been shown that both catechins and EGCG suppress PDGF-BB induced activation of PDGF-receptor mediated signal transduction pathways in VSMC by blocking tyrosine phosphorylation and their downstream molecular targets [ 99 ]. These findings are consistent with our recent study on antiproliferative effect of Gentiana lutea and its main constituent isovitexin where Kesavan et al have reported aqueous root extract of G. lutea and isovitexin significantly inhibit PDGF-BB induced proliferation of SMC by downregulation of ERK1/2 and iNOS expression [ 100 ]. Similarly in another study we have shown significant antiproliferative effect of ellagic acid (EA), phenolic compound present mainly in barriers, which might be due to prevention of PDGF-BB receptor tyrosine phosphorylation/activation, reduced ROS generation, and downstream stimulation of ERK1/2 [ 101 ].…”
Section: Role Of Phytochemicals In Cell Migration and Proliferatiosupporting
confidence: 93%
“…To this end, it may be possible to take advantage of the genomic clustering of the Tas2r to simultaneously knock out multiple receptors. Alternatively, as has been done for one TAS2R , generation of humanized mice expressing tissue‐specific human taste GPCRs may be a profitable approach in the future (69).…”
Section: Discussionmentioning
confidence: 99%
“…Cells-NO levels in L6 cells were measured by the 4,5-diaminofluorescein diacetate method as described previously (19). Briefly, L6 cells were seeded in 24-well plates.…”
Section: Measurement Of Nitric Oxide (No) Levels In Culturedmentioning
confidence: 99%